Implementation of modified current synchronous detection method for voltage control of self‐excited induction generator. Issue 7 (1st July 2015) - Singh, Bhim; Murthy, S.S.; Reddy, R.S.; Arora, Prachi
Abstract : This study presents a modified current synchronous detection method for voltage control of self‐excited induction generator (SEIG)‐based standalone power generating system using a static reactive power compensator (STATCOM). The proposed STATCOM is a three‐leg insulated gate bipolar transistor‐based voltage source inverter with self‐sustaining DC‐bus capacitor. The STATCOM offers instantaneous voltage control of SEIG through reactive power compensation. In addition to voltage control, the STATCOM also provides load balancing under unbalanced loadings and harmonics compensation while feeding non‐linear loads. The control of STATCOM is implemented using a modified current synchronous detection algorithm that uses a second‐order generalised integrator (SOGI) to filter the sensed SEIG voltages and for estimating the amplitudes of individual phase voltages. The performance of the proposed SOGI‐CSD‐based control of STATCOM is simulated in MATLAB/Simulink and verified experimentally on a developed SEIG‐STATCOM system. Test results exhibit effective harmonics suppression and load balancing capabilities of the STATCOM along with instantaneous voltage control.